Headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS) and odor activity value (OAV) to reveal the flavor characteristics of ripened Pu-erh tea by co-fermentation - Zheng, Yaru; Zhang, Chunhua; Ren, Dabing; Bai, Ruoxue; Li, Wenting; Wang, Jintao; Shan, Zhiguo; Dong, Wenjiang; Yi, Lunzhao (Frontiers in Nutrition, 2023)
In this study, ripened Pu-erh teas were obtained by different mix strains pile co-fermentation. A total of 135 volatile compounds were annotated using HS-SPME-GC-MS, of which the highest content was alcohols (54.26%), followed by esters (16.73%) and methoxybenzenes (12.69%). The total content of these compounds increased with the duration of fermentation and the diversity of the mixed strains. The flavor profiles of 27 volatile compounds with rOAVs > 1 were analyzed by relative odor activity values (rOAVs). Alcohols in ripened Pu-erh tea mainly contribute flower and fruit sweet flavors, while methoxybenzenes mainly contribute musty and stale flavors. The ripened Pu-erh tea fermented by Saccharomyces: Rhizopus: Aspergillus niger mixed in the ratio of 1:1:1 presented the remarkable flavor characteristics of flower and fruit sweet flavor, and having better coordination with musty and stale flavor. This study demonstrated the content changes of ripened Pu-erh tea’s flavor compounds in the fermentation process, and revealed the optimal fermentation time. This will be helpful to further understand the formation mechanism of the characteristic flavor of ripened Pu-erh tea, and guide the optimization of the fermentation process of ripened Pu-erh tea.